Capacity of the Regional Revenue Agency of Bekasi District in Increasing Regional Original Revenue (PAD) Through Rural and Urban Land and Building Tax (PBB-P2) - Vega Megiantary; Heru Nurasa; Sawitri Budi Utami (LP2M IAIN Palopo, 2025)
This study aims to analyze the capacity of the Bekasi Regency Regional Revenue Agency (Bapenda) in optimizing the management of Rural and Urban Land and Building Tax (PBB-P2) in order to increase Regional Original Income (PAD). In the context of regional government, the effectiveness and efficiency of regional tax management are influenced by various organizational factors. This study uses a qualitative approach to explore various dimensions of organizational capacity, such as strategic leadership, program and process management, and cooperation networks. The data used in this study came from in-depth interviews and field observations combined with secondary data from media documentation and previous research. The results of the study indicate that aspects of strategic leadership, program and process management, and cooperation networks play an important role in the effectiveness of PBB-P2 management. In the strategic leadership dimension, policy continuity and leadership stability contribute to the achievement of long-term strategic goals. In the aspect of program and process management, data-based planning and realistic targets are needed to improve the efficiency of program implementation. In addition, strengthening cooperation networks with various stakeholders can support the optimization of regional tax management.